1998
DOI: 10.1002/(sici)1521-4109(199810)10:14<959::aid-elan959>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and Electroanalysis of Copper Species at Electrochemically Activated Glassy Carbon Electrodes

Abstract: Electrochemically activated glassy carbon electrodes were applied to the preconcentration and electroanalysis of metal species. Activated glassy carbon electrodes were obtained by potentiostatic oxidation at +2.0 V in 0.5 M sulfuric acid. Copper species were readily extracted onto the modified electrode and were determined electrochemically. Voltammetric peak currents showed linear response for copper concentrations in the range between 1 to 20 μM with a large slope of 2.11 A M−1 and a correlation coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…After 10±15 cycles, there was little change in the voltammetric response. Similar results were also observed for the determination of Cu 2 and PB 2 species at PGCE [27].…”
Section: Adsorption Of Vitamin B 2 On Activated Glassysupporting
confidence: 86%
See 2 more Smart Citations
“…After 10±15 cycles, there was little change in the voltammetric response. Similar results were also observed for the determination of Cu 2 and PB 2 species at PGCE [27].…”
Section: Adsorption Of Vitamin B 2 On Activated Glassysupporting
confidence: 86%
“…It is generally accepted that the number of active adsorption sites increases with the preanodization time [15,26,27]. The increase in saturation adsorption resulted from the increase in adsorption sites.…”
Section: Effects Of Activation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-polished electrode was cycled in a 0.1 M H 2 SO 4 solution for five times in the potential range from 0 to 2 V. It is believed that the anodization of the GC surface results in a multilayer oxide film having OH groups [21]. The effects of electrochemical activation of the GC electrode surface were previously studied with XPS [22]. The activated electrode was dipped into a 0.5 M MPS/EtOH solution for four hours.…”
Section: Preparation Of the Modified Electrodementioning
confidence: 99%
“…16 The most common pretreatment methods include mechanical polishing and electrochemical polarization. 22 Shi et al 23 reported that aromatic cations and neutral species showed weak adsorption at a bare GCE, but adsorbed strongly at an EPGCE, for example dopamine, 24 1,4-naphthoquinone, riboavin, ferrocene, nitrobenzene, 25 and hydroquinone. 18 Furthermore, according to ref.…”
Section: Introductionmentioning
confidence: 99%